Population genomics in the arboviral vector Aedes aegypti reveals the genomic architecture and evolution of endogenous viral elements. Issue 7 (22nd February 2021) - Crava, Cristina M.; Varghese, Finny S.; Pischedda, Elisa; Halbach, Rebecca; Palatini, Umberto; Marconcini, Michele; Gasmi, Leila; Redmond, Seth; Afrane, Yaw; Ayala, Diego; Paupy, Christophe; Carballar‐Lejarazu, Rebeca; et al.
Abstract: Horizontal gene transfer from viruses to eukaryotic cells is a pervasive phenomenon. Somatic viral integrations are linked to persistent viral infection whereas integrations into germline cells are maintained in host genomes by vertical transmission and may be co‐opted for host functions. In the arboviral vector Aedes aegypti, an endogenous viral element from a nonretroviral RNA virus (nrEVE) was shown to produce PIWI‐interacting RNAs (piRNAs) to limit infection with a cognate virus. Thus, nrEVEs may constitute a heritable, sequence‐specific mechanism for antiviral immunity, analogous to piRNA‐mediated silencing of transposable elements. Here, we combine population genomics and evolutionary approaches to analyse the genomic architecture of nrEVEs in A. aegypti . We conducted a genome‐wide screen for adaptive nrEVEs and searched for novel population‐specific nrEVEs in the genomes of 80 individual wild‐caught mosquitoes from five geographical populations. We show a dynamic landscape of nrEVEs in mosquito genomes and identified five novel nrEVEs derived from two currently circulating viruses, providing evidence of the environmental‐dependent modification of a piRNA cluster. Overall, our results show that virus endogenization events are complex with only a few nrEVEs contributing to adaptive evolution in A. aegypti .